Consent to care of persons with intellectual disability in Quebec:from vulnerability to capability - Chantal Caux; Jocelin Lecomte (Instituto Nacional de Salud Pública, 2017)
Persons with an intellectual disability (ID) who interact with the Quebec health and social services system are faced with major decisions regarding the care they are offered. As consent to care derives from the fundamental right of all persons to personal inviolability and to autonomous decision making, they therefore have the right to accept or refuse any and all health and psychosocial care proposed. However, as free and informed consent to care must be given by an able person, the situation becomes somewhat more complicated whereas persons with ID are concerned. This article presents reflections on the challenges and issues relative to these persons'consent to health and psychosocial care.